Centering Panama in Global Modernity: The Search for National Identity and the Imagining of the Orient in Rogelio Sinán’s “Sin novedad en Shanghai” - Junyoung Verónica Kim (Studies in 20th & 21st Century Literature, 2013)
Since its independence from Colombia in 1903 backed by the United States government, which resulted in a treaty that granted the US free rein to build, administer and control what would be known as the Panama Canal, Panama’s quest for modern nationhood has been severely called into question. More often than not it is posited as an artificial state with little organic unity and limited sovereignty: a state that is literally made in the USA. Panamanian intellectuals, such as Rogelio Sinán, responded to these discourses on the Panamanian nation-state by actively constructing a Panamanian national identity, and by calling attention to the central significance of Panama in the twentieth-century world of global modernity. Questioning the widespread narrative of Panama as a peripheral North American neo-colony that was at best a marginal actor in international history, Sinán positioned Panama at the center of the modern world where World Wars, international migrations and global capitalism connected. By exploring Sinán’s short story “Sin novedad en Shanghai” that takes place in East Asia during World War II, this study argues that the writer’s deployment of the Orient—as a geopolitical, cultural, symbolic and imaginary space—allows him to reposition Panama. In its symbolic relation to this Orient, Panama emerges not as the backwaters of global modernity, but at its center—a cosmopolis between the Orient and the Occident that reveals a microcosm of the modern world.
Keywords: Panama; Rogelio Sinán; Sin novedad en Shanghai; Panamanian discourse; national identity; global modernity; neo-colony; global capitalism; orient; repositioning; occident; modern world